The Impact of Cancer Disease on the Families of the Patient, A Case Study of the Pediatric Wing, Cancer Disease Hospital in Lusaka, Zambia - Pupwe, George; Mugoba, Jeff; Simwanza, Niza Rean (International Journal of Health Sciences, 2025)
Purpose: Globally, cancer casts a heavy shadow. An estimated 12.7 million new cases are diagnosed annually, with about 7.6 million deaths attributed to the disease. Notably, low- and middle-income countries (LMICs) bear a disproportionate burden – over half of all new cases and a staggering two-thirds of cancer deaths occur in these regions. While advancements have been made, with 5-year survival rates exceeding 80%, the fight against childhood cancer continues. Many children still tragically succumb to the disease even after this initial milestone. In fact, cancer is the leading cause of death from illness in children. This research aimed to investigate the impact of cancer disease on the families of the patient, a descriptive analysis of the pediatric wing, cancer disease hospital Lusaka, Zambia. Methodology: The study identified five major themes reflecting the impact of cancer on patients' families. Emotional burden accounted for 31%, financial strain 30%, healthcare system challenges 25%, coping mechanisms 9%, and social isolation 6%. The majority of participants were female (88%), consistent with traditional caregiving roles. Most participants came from low-to-middle-income households, underscoring financial strain as a significant caregiving challenge. Participants' ages ranged from 21 to 61 years, with the largest group (34%) being in the 36-50 age range. Findings: These findings underscore the urgent need for comprehensive, caregiver-centric interventions that addressing both immediate caregiving needs and a broader systemic gap in healthcare and community support for the caregivers of the children suffering from cancer at Cancer Disease Hospital in Lusaka, Zambia. Unique Contribution to Theory, Policy and Practice: By taking actionable steps, policymakers and public health practitioners can significantly improve the well-being of caregivers and the outcomes for the children they care for.